The Development of Anesthesiology Nursing Practice Guidelines in Patients with Hemorrhagic Stroke at Undergo Surgery Samut Sakhon Hospital - Somboonjan, Orawan; Eaimimsumran , Watcharee; Tawatwa, Suda; Chawisthitanan, Pimsiri (Journal of Nursing, Siam University, 2023)
This research and development aimed to develop and study the results of using anesthesia nursing practice guidelines in patients with hemorrhagic stroke has undergone surgery at Samut Sakhon Hospital. The researcher developed it using empirical evidence that was conducted accordingly. Empirical evidence steps by using the research results of the IOWA Model (IOWA Model Collaborative, 2017). The target group consists of service providers, including anesthesia nurses, 19 people, professional nurses working in unit, 58 people, and service recipients, including patients who have been diagnosed, 30 people had hemorrhagic stroke and were treated with surgery at Samut Sakhon Hospital. Results of the study: Anesthesia nursing practice guidelines for patients with hemorrhagic stroke has undergone surgery at Samut Sakhon Hospital developed from empirical evidence in 20 cases. Evaluate the level of empirical evidence using Mellin’s criteria. And power out – overhaul Empirical evidence Level 2:3 stories. Level 3:2 stories, Level 4:4 stories, Level 5:5 stories, Level 6:2 stories, and Level 7:4 stories. The practice guideline consists of nursing 3 phases: 1) the pre-anesthesia phase; Including preparing patients for anesthesia nurses. and preparing patients for professional nurses in the unit. 2) during anesthesia; Including nursing during anesthesia, anesthesia, and nursing during recovery from anesthesia. 3) after anesthesia; Including post-anesthesia nursing for anesthesia nurses, visit patients after receiving anesthesia in the ward. and post-anesthesia nursing for professional nurses in the unit. Evaluate the practical ability of anesthesia nurses in the unit at a high level when used by service recipients who are patients with hemorrhagic stroke of the 30 people who received surgery, no incidence of discrepancies was found in postponing surgery not ready and unplanned transfer to intensive care unit and no complications were found from the suppression of feelings.